Local resectability assessment of head and neck cancer: Positron emission tomography/MRI versus positron emission tomography/CT. Issue 8 (13th May 2017) - Sekine, Tetsuro; Barbosa, Felipe de Galiza; Delso, Gaspar; Burger, Irene A.; Stolzmann, Paul; ter Voert, Edwin E.; Huber, Gerhard F.; Kollias, Spyros S.; von Schulthess, Gustav K.; Veit‐Haibach, Patrick; Huellner, Martin W.
Abstract: Background: The purpose of this study was to compare the diagnostic accuracy of positron emission tomography (PET)/MRI with PET/CT for local resectability of head and neck cancer. Methods: Sequential contrast‐enhanced PET/CT‐MRI was performed in 58 patients referred for the staging or restaging of head and neck cancer. Tumors were assessed with PET/CT and PET/MRI for the presence of resectability‐defining factors: T4b status (mediastinal invasion, invasion of the prevertebral space, and vascular encasement), and another 8 findings that would imply obstacles for surgical cure (invasion of the laryngeal cartilage, invasion of the preepiglottic fat pad, perineural spread, orbital invasion, bone infiltration, skull base invasion, dural infiltration, and invasion of the brachial plexus). Results: The sensitivity/specificity/accuracy of local resectability‐defining factors of PET/CT and PET/MRI was 0.92/0.99/0.98 and 0.98/0.99/0.99 ( P = .727), respectively, per lesion, and 0.96/0.87/0.91 and 0.96/0.90/0.93 ( P = .687), respectively, per patient. Conclusion: Both contrast‐enhanced PET/MRI and contrast‐enhanced PET/CT can serve as reliable examinations for defining local resectability of head and neck cancer.